A fé cristã na era digital : diálogo entre a revelação na teologia de Bruno Forte e a experiência religiosa na internet - Andreolla, Jurema (2012)
New possibilities are offered to religion in the society now, which is marked by information culture, digital media and virtuality. Thus, we asked: is it possible to make a hearing experience and to maintain a dialogue with God through the new ambience of faith, created by the Internet? In the light of Brono Forte s theological ideas, the current study is part of the Christian Revelation that was carried out to demonstrate what is the dialogue that is mediated by faith, experienced in Digital Era. Therefore, we used exodus and advent categories, in order to demonstrate how the author develops his conception of the situation of man, considering God and neighbor in the plan of faith. After that, we identified how people look for experience with God in media of communication, particularly in the new social networking sites. We verified that some questions arise, through the development of the present study: Is it possible to find God in virtual space? Can a community of face be considered a space of evangelization and community of experience? Finally, through a qualitative research, we identified categories that express a Christian religious experience that use internet with this purpose. We concluded that there is dialogue between Theology and Communication, if we consider Bruno Forte s ideas, confronted to the results of the interviews.